PYRUS ZANGEZURA (ROSACEAE) AT SAINT PETERSBURG - K. G. Tkachenko; G. A. Firsov; L. F. Yandovka; A. V. Volchanskaya; N. E. Staroverov; Yu. A. Gryaznov (Труды по прикладной ботанике, генетике и селекции)
Pyrus zangezura Maleev (Rosaceae) is a rare species representing the native vegetation of Armenia (Southern Transcaucasus). It was first described in 1936. P. zangezura has been cultivated at the Peter the Great Botanical Garden of the Komarov Botanical Institute (St. Petersburg, Russia) since 1949, where it has reached the height of 8,0 m. For many years, it was in its vegetative state. The first flowering was observed in 2016 (the plant entered the reproductive state). The first progeny from seed was obtained in April 2019. Fruit size was assessed for P. zangezura plants in the dynamics of their development. The studied plants of P. zangezura in the environments of St. Petersburg have demonstrated a high fruiting potential – on average, 109 flowers per 1 m of a shoot. Observations have shown that not all ovules in the opened flowers of P. zangezura are fertilized and produce fruits and seeds. A significant part of the opened flowers, a few days after the onset of flowering, dry up and fall off. On average, 7 fruits are set on 1 m of the shoot in P. zangezura. The reasons for the low flower setting may be variable: impaired pollination processes and insufficient fertility of pollen, underdevelopment of the flower morphological structures, or lack of pollinating insects due to adverse weather conditions. An X-ray analysis of the seeds from the harvests of 2016, 2017 and 2018 showed that the number of plump and fully developed seeds (grades IV and V) in fruits has been growing year by year. As an ornamental plant, P. zangezura may adorn any botanical garden, but it is also promising for urban landscaping, for example, in St. Petersburg. Even in the vegetative state, its elongated lanceolate glossy leaves make it appreciably different from the common P. communis L., and it is especially ornamental during flowering and fruiting. It is as winter-hardy as the common pear-tree, demonstrates resistance to diseases and pests, and may be of importance for breeding programs aimed at the development of resistant cultivars for the Northwest of Russia.